Would you come back to visit Malaysia? Understanding tourists perceived risks towards revisit desire - Koo Tiam Chin; Zufara Arneeda Zulfakar; Nor Haliza Che Hussain (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Due to major contributions of the tourism industry towards the economy a country, it is important to ensure that Malaysia is able to continuously attract visitors to the country. This paper aims to look into the tourists perceived risk namely their perception on financial risk, physical risk, socio-psychological risk and time risk in Malaysia and their desire and intention to revisit Malaysia in the future. The results of this study have shown that the tourists who have visited Malaysia have intention to revisit the country despite their a slightly high perception of risks in Malaysia. Financial risk that has shown statistical significance influence towards the revisit desire. Such results may be useful for those in the industry to prepare in attracting tourists to visit Malaysia once the travel bans are lifted and international borders are re-open